Management of Hairy Tongue With Oral Candidiasis In Active Smokers - Sri Hernawati (Health Notions, 2020)
Hairy tongue is an abnormal lengthening of the filiform papillae of the tongue, clinically the dorsum of the tongue looks hair-coated. The etiology of hairy tongue is idiopathic. Predisposing factors for hairy tongue are poor oral hygiene, antibiotics, excessive smoking, oral candidiasis, alcohol consumption, radiation therapy. Candidiasis is an opportunistic infection of the oral cavity caused by Candida albicans (C. albicans). This fungus can cause a pathogenic condition, and is the most common fungal infection found in the human oral cavity. Predisposing factors for oral candidiasis are the use of dentures, xerostomia, stress, and smoking habits. Objective: To demonstrate the management of a case of hairy tongue with oral candidiasis on the dorsum of the tongue. Case: A 54-year-old male patient came to the Dental Hospital of Jember University for treatment with a complaint of feeling thick and yellowish-brown color on the back of the tongue with clinical features of an extension of the papillae filiformis in the posterior third of the dorsum of the tongue, and a white-yellowish white plaque, could be scraped, but not sick. The patient had complained it since ± 3 years ago. The patient claimed to have never had his tongue scraped off and never treated it. In addition, he smoked a pack of cigarette a day and consumed coffee every morning and evening. Conclusion: The final diagnosis in the patient was hairy tongue with oral candidiasis on the dorsum of the tongue. Therapy provided to the patient i.e. Nystatin oral suspension functions as a topical antifungal medication, Becomzet multivitamin (Vitamin B complex, A, C, E, and Zinc) as a multivitamin and Tongue cleaner as a tongue cleaner. Dental and oral health education was conducted for preventing hairy tongue. Keywords: hairy tongue; oral candidiasis; active smokers